Price Imputation and Other Techniques for Dealing with Missing Observations, Seasonality and Quality Change in Price Indices - Armknecht Jr., Paul (IMF Working Papers; Working Paper, 1999)
Price index compilers frequently face situations where price observations are missing due to seasonal unavailability, supply shortages, or the discontinuation of products. Incorrect treatment of such situations can result in biased price indices. This paper presents statistical imputation techniques that index compilers can use to prevent bias and suggests the extension of these same techniques to assist with adjustments for quality differences. The use of additional procedures for dealing with some of the problems caused by seasonal commodities is also discussed.